Role of the Complement System in the Pathogenesis of Venous Thromboembolism - Høiland, Ina Isabella (UiT The Arctic University of Norway, 2019)
Venous thromboembolism (VTE) is a common disease with serious short- and long-term complications. VTE is a collective term for deep vein thrombosis (DVT) and pulmonary embolism (PE) and is the third most common cardiovascular disease, causing significant morbidity and mortality. Despite preventive strategies, the incidence of VTE has been stable or increasing slightly during the last decades, affecting 1-2 per 1000 individuals each year. Identifying new biomarkers and unraveling underlying mechanisms might help diminish the health burden of VTE. The complement system is a cascade system similar to the coagulation system. The two systems have a high degree of crosstalk and are activated together in many conditions. Polyphosphates (polyPs) are naturally occurring, highly anionic linear polymers of monophosphate units. Short-Chained (SC)-PolyPs are stored and secreted from platelets upon stimulation and are reported to inhibit complement activation and to facilitate propagation of coagulation activation under experimental conditions. This indicates that SC-polyP might modulate the possible link between the two systems, and play a role in the pathogenesis of VTE. The main goals of this thesis were to assess the association between complement activation and VTE risk, and to investigate the role of SC-polyPs in the activation of these two systems. In paper I, we performed a case-control study to investigate the association between potential complement activity and VTE risk. We found that individuals with high potential activity of the classical pathway of the complement system and individuals with MBL deficiency had higher risk for VTE. In paper II, we conducted a nested-case-control study derived from a population-based cohort (The Tromsø Study) to investigate the relationship between complement activation and future risk of VTE. We found that high degree of complement activation, assessed by plasma terminal complement complex (TCC), was associated with increased risk of VTE, and especially unprovoked VTE. Results ...